A state of art review and future viewpoint on advance cooling techniques for Lithium–ion battery system of electric vehicles. (December 2020) - Thakur, Amrit Kumar; Prabakaran, Rajendran; Elkadeem, M.R.; Sharshir, Swellam W.; Arıcı, Müslüm; Wang, Cheng; Zhao, Wensheng; Hwang, Jang-Yeon; Saidur, R.
Abstract: Electric Vehicles (EVs) have emerged as most promising means of transport owing to the low operational costs, high speed, and energy-efficient battery technologies, where battery thermal management system (BTMS) is possibly the most crucial element of an EV. During the charging/discharging mode of EVs, a major focused area for the researcher is to maintain the optimal working temperature range of the batteries and reduce both the maximum temperature and temperature difference. Suitable and effective cooling methods can significantly reduce the adverse effect of the high surface temperature of battery cells and efficiently augments the battery thermal efficiency, improves the safety of EVs, and increase the service life. In this context, this work presents a detailed state of the art review of different BTMS technologies, including natural and forced air-cooling techniques, direct and indirect liquid cooling methods, and cooling by heat pipes. It is found that the air-cooled BTMS possesses advantageous features such as safe, consistent, and simple design, but the lower heat capacity and thermal efficiency of the air as a cooling medium restricts its application to a low capacity battery. This leads to employment of forced air-cooled BTMS under high charging/discharging rate, in which air flows through the channels inside the battery packs to provide the optimum cooling. Liquid-cooled BTMS is also emerging as one of the most promising cooling technologies, which requires attention to the sealing cover during the design stage to avoid leakages. The integration of metal plates with the mini channel can effectively improve the cooling performance, but the weight of the system is a major concern. Liquid metals, nanofluids, and boiling liquids are considered as the most prominent battery cooling methods owing to their higher thermal conductivity. The advancement in hybrid cooling using fins, nanofluids, PCM along with micro channels-based cooling will significantly improve the battery performance under high charging/discharging rate and attention should be given to compact design with a cheaper cost.